A Randomized Study on the Prophylactic Use of Acetaminophen to Prevent Fever after the Removal of Drainage Tubes for Lumbar Surgery. Issue 2 (29th November 2022) - Ye, Kaifeng; Li, Yan; Xing, Yong; Liu, Kaixi; Zhou, Fang; Tian, Yun; Zhang, Yanping
Abstract : Background: Many inpatients encounter a fever in the first 24 h after drainage removal. It is costly to exclude the possibility of deep infection and cultures usually fail to identify the etiology. We hypothesize that the fever is caused by a normal inflammatory response and tested whether the prophylactic use of acetaminophen could reduce the fever rate. Methods: This was a prospectively randomized clinical trial performed from July 2019 to January 2020. A total of 183 consecutive patients undergoing lumbar spine surgery were prospectively randomized into two groups. Ninety‐one patients were randomized into the study group; they received oral acetaminophen before removal of the drainage tubes and a second dose at 8 p.m. on the same day. The remaining 92 patients were placed in the control group, and they were given routine treatment without acetaminophen. The two groups were compared for differences in age, sex, height, weight, BMI, surgical segments, surgical time, blood loss, blood transfusion, ASA score, duration of drainage, total volume of the drainage, variation of WBC and CRP, hospital stay after the removal of the drainage tube and the rate of fever. Student's t ‐test and the Mann–Whitney U test were used to analyze the continuous data, while the chi‐square test was used for the analysis of the ranked data. Results: Regarding the comparisons of basic information, there were no significant differences between the two groups for age, height, weight, BMI, surgical segments, surgical time, blood loss, blood transfusion, total drainage volume, duration of drainage, hospital stay, WBC, and CRP variation or the duration of hospital stay after removal of the drainage tube (all p  > 0.05). However, the fever rate was significantly different ( p  = 0.006), and the fever rate of the study group (14/91, 15.38%) was significantly lower than that of the control group (30/92, 32.61%). In the study group, there were no complications related to the use of acetaminophen during the hospital stay or during the outpatient follow‐up period. Conclusion: Fever after removal of tube drainage is caused by a normal inflammatory response, and a small dose of acetaminophen could significantly reduce the possibility of fever. Abstract : Fever after the removal of tube drainage was caused by normal inflammation response, the inflammatory cytokines could stimulate the preoptic area of the hypothalamus to increase prostaglandin production, and then raise the thermoregulatory set point for body temperature, a small dose of acetaminophen could block this process.